2012
DOI: 10.1074/jbc.m112.362020
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Zfand5 Binds and Stabilizes mRNAs with AU-rich Elements in Their 3′-Untranslated Regions

Abstract: Background: AU-rich elements (AREs) in the 3Ј-UTR of mRNA confer instability; the mechanisms are incompletely understood.Results: A genomic screen identified Zfand5 as a stabilizer of ARE-RNA. Conclusion: Zfand5 enhances ARE-RNA stability by competing with TTP for mRNA binding. Significance: A better understanding of ARE-RNAs regulation is of clinical significance because many inflammatory mediator transcripts contain ARE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(58 reference statements)
1
14
0
1
Order By: Relevance
“…6B/C). Apart from TIS11 family proteins we also investigated mRNA expression of the recently discovered Zfand5, a protein stabilizing ARE-containing transcripts [13]. While we found a higher expression of Zfand5 transcript in RAW macrophages than in WT BMMCs that were either untreated or stimulated with LPS for 1 h, after 3 h of LPS treatment mRNA expression of Zfand5 was comparable between the different cell types (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…6B/C). Apart from TIS11 family proteins we also investigated mRNA expression of the recently discovered Zfand5, a protein stabilizing ARE-containing transcripts [13]. While we found a higher expression of Zfand5 transcript in RAW macrophages than in WT BMMCs that were either untreated or stimulated with LPS for 1 h, after 3 h of LPS treatment mRNA expression of Zfand5 was comparable between the different cell types (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Exemplarily, the ubiquitous nuclear protein HuR has been shown to bind to ARE-containing transcripts, thereby increasing their half-life [12]. HuR and the recently discovered ARE-binding protein Zfand5 bind to the AREs in the TNF-α mRNA, competitively counteracting the effect of TTP binding and thus leading to stabilization and enhanced translation of the TNF-α transcript [13, 14]. The balance between mRNA stabilizing and destabilizing proteins competing for the same ARE sites adds another layer of regulation to the overall translation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have found that ZFAND2A expression is induced by arsenite (114,115) and heat shock (116). Similarly in macrophages, ZFAND5 expression is induced by cell stress in response to TNF, IFNg, LPS, and other toll-like receptor ligands (117)(118)(119). ZFAND5 also can compete with zinc finger protein 36 (aka tristetraprolin) and stabilizes class II adenylate/ uridine-rich sequence element containing mRNA, a region common to inflammatory mediator transcripts including TNF mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…ZFAND5 also can compete with zinc finger protein 36 (aka tristetraprolin) and stabilizes class II adenylate/ uridine-rich sequence element containing mRNA, a region common to inflammatory mediator transcripts including TNF mRNA. Thus, ZFAND5 is induced by and stabilizes TNF (119). However, the role of these proteins in ALI must be viewed with caution because structural similarity does not predict functional similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Сверхэкспрессия ZFAND5 делает клетки чувствительные к TNF-индуцированному апоптозу. Ген ZFAND5 может быть вовлечен в регуляцию активации NF-kappa-B и апоптоза [17]. Сверх экспрессия генов ZFAND5 и GREB1 делает клетки чувствительные к TNF-индуцированному апоптозу, который опосредуется каспазой 8 и 3, тогда как низкая экспрессия этих генов препятствует индукции программированной клеточной смерти.…”
Section: а) б)unclassified